Increase in gut permeability and oxidized ldl is associated with post-acute sequelae of SARS-CoV-2 - Christian Mouchati; Jared C. Durieux; Sokratis N. Zisis; Danielle Labbato; Michael A. Rodgers; Kate Ailstock; Brian L. Reinert; Nicholas T. Funderburg; Grace A. McComsey; Grace A. McComsey (Frontiers in Immunology, 2023)
BackgroundPost-acute sequelae of SARS-CoV-2 (PASC) is marked by persistent or newly developing symptoms beyond 4 weeks of infection. Investigating gut integrity, oxidized lipids and inflammatory markers is important for understanding PASC pathogenesis.MethodsA cross-sectional study including COVID+ with PASC, COVID+ without PASC, and COVID-negative (COVID-) participants. We measured plasma markers by enzyme-linked immunosorbent assay to assess intestinal permeability (ZONULIN), microbial translocation (lipopolysaccharide-binding protein or LBP), systemic inflammation (high-sensitivity C-reactive protein or hs-CRP), and oxidized low-density lipoprotein (Ox-LDL).Results415 participants were enrolled in this study; 37.83% (n=157) had prior COVID diagnosis and among COVID+, 54% (n=85) had PASC. The median zonulin among COVID- was 3.37 (IQR: 2.13, 4.91) mg/mL, 3.43 (IQR: 1.65, 5.25) mg/mL among COVID+ no PASC, and highest [4.76 (IQR: 3.2, 7.35) mg/mL] among COVID+ PASC+ (p<.0001). The median ox-LDL among COVID- was 47.02 (IQR: 35.52, 62.77) U/L, 57.24 (IQR: 40.7, 75.37) U/L among COVID+ No PASC, and the highest [76.75 (IQR: 59.95, 103.28) U/L] among COVID+ PASC+ (p<.0001). COVID+ PASC+ was positively associated with zonulin (p=0.0002) and ox-LDL (p<.0001), and COVID- was negatively associated with ox-LDL (p=0.01), compared to COVID+ No PASC. Every unit increase in zonulin was associated with 44% higher predicted odds of having PASC [aOR: 1.44 (95%CI: 1.1, 1.9)] and every one-unit increase in ox-LDL was associated with more than four-fold increased odds of having PASC [aOR: 2.44 (95%CI: 1.67, 3.55)].ConclusionsPASC is associated with increased gut permeability and oxidized lipids. Further studies are needed to clarify whether these relationships are causal which could lead to targeted therapeutics.